Ultrathin flexible glass with lossless chamfer and preparation method thereof

By forming controlled chamfers at the junction of ultra-thin flexible glass and fixing with extremely fine fiber lines, the problem of stress concentration and insufficient bending times is solved, and ultra-thin flexible glass with high strength and excellent bending performance is achieved.

CN119241083APending Publication Date: 2025-01-03凯盛科技股份有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411189781.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing ultra-thin flexible glasses are severely stressed during dynamic bending, with limited bending times, and are prone to damage and concave point damage during etching.

Method used

By forming an upper chamfer and a lower chamfer between the upper plane and the end surface and the lower plane of the ultra-thin flexible glass, the ratio of the chamfer width to the thickness of the glass is controlled to be between 0.3-0.5, and extremely fine fiber lines are used as The rack of the basket is fixed, and chamfered with etching liquid of hydrofluoric acid and inorganic acid to form ultra-thin flexible glass with non-destructive chamfered.

Benefits of technology

It effectively reduces stress concentration, improves the number of bends and impact resistance, avoids concave points damage during etching, and improves the overall strength and bending performance of the glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241083A_ABST
    Figure CN119241083A_ABST
Patent Text Reader

Abstract

The invention provides ultra-thin flexible glass with a lossless chamfer and a preparation method of the ultra-thin flexible glass. The ultra-thin flexible glass comprises an upper plane, a lower plane and an end face for connecting the upper plane and the lower plane, wherein the junction between the upper plane and the end face is provided with an upper chamfer part, and the junction between the lower plane and the end face is provided with a lower chamfer part; each of the upper chamfered portion and the lower chamfered portion has a chamfer width / glass thickness ratio < 0.5. According to the ultrathin flexible glass with the lossless chamfer and the preparation method of the ultrathin flexible glass, on one hand, by controlling the chamfer size of the ultrathin flexible glass to be optimal, stress concentration of UTG in dynamic bending is effectively reduced, the bending frequency is increased, and the bending performance is improved; and on the other hand, the single glass is clamped and fixed by the basket with the superfine fiber lines serving as the racks, and the chamfer is formed by etching, so that the defect that the laminated glass is easy to damage due to separation is avoided, and the defect that the surface of the chamfer of the glass supported by the basket is damaged due to concave points is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of glass processing, and in particular to an ultra-thin flexible glass with lossless chamfering and a preparation method thereof. Background Art

[0002] As a common inorganic non-metallic material, glass has high transparency, chemical stability, hardness and heat resistance, and is easy to process, making it suitable for various fields such as construction and electronic display. After the thickness of glass is reduced to 0.1mm, it will show good flexibility and can realize bending function. This kind of glass is called ultra-thin flexible glass (UTG). With the advancement and innovation of science and technology, the application fields of flexible glass are also constantly optimized and expanded: the outstanding scratch resistance, oxidation resistance and high transmittance of flexible glass can be used as a cover material for flexible display; the high temperature resistance of flexible glass makes it adapt to the high temperature environment of optoelectronic and semiconductor device processing. At the same time, the most significant bending performance of flexible glass makes it possible to use continuous "roll-to-roll" printing process to prepare various optoelectronic devices; flexible glass can also be used to manufacture bendable and foldable solar photovoltaic panels, providing more application possibilities for solar power generation.

[0003] Many application scenarios of UTG have put forward higher requirements for its own performance. The glass thickness and its uniformity, surface roughness, appearance transmittance, shape, and internal and external stress values ​​all affect the use effect. Patent CN115259680A discloses a thinning device suitable for UTG products to improve the problem of large thickness difference of glass during thinning molding, so that the thickness deviation of the entire plate after glass thinning is controlled below 10μm, laying the foundation for subsequent performance processing of glass. Patent CN114933419A discloses a method for preparing UTG using a bionic weathering enzyme composite glass thinning agent, which can control the surface roughness Ra of the glass to be lower than 10nm and improve the appearance transmittance of the glass. Patent US20150165548A discloses a process for chamfering and / or chamfering the edges of glass or other substrates of arbitrary shapes using a laser, aiming to eliminate defects, make the edges have a more uniform surface, and improve the overall strength of the glass.

[0004] The presence of UTG chamfers can greatly alleviate its stress concentration phenomenon, and at the same time can repair the broken edges and microcracks formed in the glass during mechanical processing. Patent CN111601780A discloses a chemically tempered glass product with a thickness of less than 0.4mm, wherein the compressive stress on the glass surface is greater than 200MPa, the ratio of the chamfer width to the chamfer height is between 1.5-20, and the ratio of the chamfer width to the glass thickness is at least 0.5, so as to improve the bending strength of the glass, but it is not effective in reducing the stress concentration of UTG in dynamic bending and increasing the number of bends; in addition, the chamfering processing method mentioned is to stack several pieces of UTG together through polymers, and the edges of the stacks are mechanically ground by CNC to generate stacked ultra-thin glass without chamfers, and then the stacks are immersed in an etching solution to form chamfers, but the stacked glass is at high risk of breakage during subsequent separation. Patent CN114031301A forms an acid-resistant organic protective layer on the surface of the single-layer glass outside the cutting surface, and forms a chamfer after immersing it in an etching solution. However, for ultra-thin flexible glass with a thickness of less than 0.1mm or even less than 0.05mm, the single-layer glass cannot stand upright without external support and needs to be fixed by a fixture. In order to ensure the uniformity of etching, most people now choose to use a basket to fix the glass. The lower edge of the glass will form a concave point size due to long-term contact with the teeth of the basket, causing stress concentration, which will reduce the edge strength and overall bending strength of the glass, affecting the use effect of UTG. Summary of the invention

[0005] Based on the technical problems existing in the background technology, the present invention proposes an ultra-thin flexible glass with lossless chamfer and a preparation method thereof. On the one hand, by controlling the chamfer size of the ultra-thin flexible glass to be optimal, the stress concentration of UTG in dynamic bending is effectively reduced, the number of bending times is increased, and the bending performance is improved; on the other hand, a single piece of glass is fixed by a basket having extremely fine fiber wires as racks to etch and form a chamfer, which not only avoids the defect of easy damage due to separation of laminated glass, but also eliminates the defect of concave damage on the chamfered surface of the glass supported by the basket.

[0006] The present invention provides an ultra-thin flexible glass with lossless chamfers, comprising an upper plane, a lower plane, and an end face connecting the upper plane and the lower plane; wherein the junction between the upper plane and the end face has an upper chamfered portion, and the junction between the lower plane and the end face has a lower chamfered portion;

[0007] The ratio of the chamfer width / glass thickness of the upper chamfered portion and the lower chamfered portion is less than 0.5.

[0008] For those skilled in the art, since there are edges and corners at the junction of the upper and lower surfaces and the end face of the ultra-thin flexible glass, stress is easily concentrated here, which can easily cause breakage. However, if this place is chamfered to form a chamfered portion, breakage starting from this place can be effectively avoided. In the present invention, the chamfered portion formed at the junction between the upper plane and the end face is called an upper chamfered portion, and the chamfered portion formed at the junction between the lower plane and the end face is called a lower chamfered portion. By controlling the ratio of the chamfer width / glass thickness of the upper chamfered portion and the lower chamfered portion to be less than 0.5, the inventors found that it is not only beneficial to reduce the stress concentration of UTG in dynamic bending and increase the number of bending times, but also the obtained UTG finished product has higher impact resistance and excellent bending performance.

[0009] Preferably, the glass thickness is ≤0.1 mm, preferably ≤0.07 mm, and more preferably ≤0.03 mm.

[0010] Preferably, the chamfer width of the upper chamfered portion is defined as W, the chamfer width of the lower chamfered portion is defined as W', and the glass thickness is defined as T; 0.3≤W / T<0.5, and 0.3≤W' / T<0.5;

[0011] Preferably, 0.4≤W / T<0.5, and 0.4≤W′ / T<0.5.

[0012] In the present invention, the ratio of chamfer width to glass thickness is further controlled to be ≥ 0.3, so as to avoid damage caused by excessive concentration of external force on the chamfer surface due to the chamfer width being too small.

[0013] Preferably, the upper chamfered portion and the lower chamfered portion have an inclined surface or a curved surface which gradually protrudes outward from the upper plane or the lower plane toward the middle portion of the end surface.

[0014] Preferably, the surface pit size of the upper chamfered portion and the lower chamfered portion is ≤0.01 mm.

[0015] The present invention also provides a method for preparing an ultra-thin flexible glass with lossless chamfers, comprising the following steps:

[0016] S1. After coating the upper and lower surfaces of the ultra-thin flexible glass substrate to form an acid-resistant protective coating, cutting to form a desired shape;

[0017] S2, after the cut ultra-thin flexible glass substrate is completely immersed in the etching solution, the junctions of the upper plane and the lower plane with the end face are etched to form an upper chamfered portion and a lower chamfered portion;

[0018] S3, removing the acid-resistant protective coating on the upper plane and the lower plane of the etched ultra-thin flexible glass substrate to obtain the ultra-thin flexible glass.

[0019] In the present invention, firstly, an acid-resistant protective coating is coated on the upper plane and the lower plane of the ultra-thin flexible glass substrate to protect the glass substrate; then, an etching liquid is used to etch the glass substrate covered with the acid-resistant protective coating, and the junctions between the upper plane and the lower plane of the glass substrate and the end face are gradually dissolved by the etching liquid to form an upper chamfered portion and a lower chamfered portion; finally, the acid-resistant protective coating on the upper plane and the lower plane of the etched ultra-thin flexible glass substrate is removed to obtain the ultra-thin flexible glass.

[0020] Preferably, in step S1, the acid-resistant protective coating is formed by UV curing of a high molecular weight acid-resistant organic material;

[0021] Preferably, the high molecular weight acid-proof organic material is an acrylate-based free radical polymerization resin or an epoxy-based cationic polymerization resin.

[0022] Preferably, in step S2, the cut ultra-thin flexible glass substrate is fixed by inserting into a basket and then immersed in an etching solution;

[0023] Preferably, the rack at the lower end of the basket in contact with the edge of the ultra-thin flexible glass substrate is a polymer organic fiber line, and the polymer fiber line is preferably a polyethylene fiber line or a polypropylene fiber line, and the diameter of the polymer organic fiber line is preferably ≤1 mm.

[0024] In the present invention, during the process of forming chamfers on ultra-thin flexible glass by etching, if a conventional basket is used to clamp and fix the glass, since the rack is relatively thick, when the edge of the glass contacts the rack for a long time, the rack hinders the etching of the contact part, resulting in the generation of pits, which may cause stress concentration and reduce the overall strength of the ultra-thin flexible glass. However, when the rack at the lower end of the basket that contacts the edge of the glass adopts an extremely fine polymer organic fiber line, the contact area between the rack and the glass can be reduced, thereby effectively avoiding pit damage.

[0025] Preferably, in step S2, the etching solution comprises hydrofluoric acid and an inorganic acid, and the inorganic acid is at least one of sulfuric acid, hydrochloric acid or nitric acid;

[0026] In the present invention, the hydrofluoric acid in the etching solution contains extremely strong electrophilic particles H + and medium electrophilic particle F - , has a strong decomposition ability on glass, and can react with the oxide on the surface of glass to form fluorosilicate, which can be well dissolved in the etching solution; inorganic acid can provide H + The etching rate can be regulated and a synergistic effect can be exerted with hydrofluoric acid to improve the etching effect. It can be seen that the above etching solution can corrode the glass, and through chemical corrosion, the glass can be chamfered into a preset size, which significantly improves the strength and bending resistance of the glass.

[0027] Preferably, the etching solution further comprises a water-soluble crown ether;

[0028] Preferably, the water-soluble crown ether is obtained by ring-opening bonding of 4'-aminobenzo-18-crown-6 and 3-glycidyloxypropyltrimethoxysilane;

[0029] In the present invention, the trimethoxysilane contained in the water-soluble crown ether can be hydrolyzed and adsorbed on the glass surface, and the crown ether group contained in the trimethoxysilane can also complex metal ions. Therefore, when the glass is etched by hydrofluoric acid to form metal ions in fluorosilicate, the metal ions can be complexed by the water-soluble crown ether, thereby forming a monolayer film composed of crown ether complex molecules on the glass surface, avoiding excessive etching at a certain place, and finally achieving the purpose of regulating the roughness of the etched surface of the chamfered part not exceeding 1.5μm, thereby achieving the purpose of further improving the bending performance of the glass.

[0030] Preferably, the etching temperature is 20-40°C and the time is 30-60s;

[0031] Preferably, during the etching process, a circulation pump is used to drive the etching solution to circulate up and down.

[0032] In the present invention, a circulation pump is used to drive the etching liquid to circulate up and down, thereby enhancing the etching efficiency and greatly shortening the time for the basket to clamp and fix the glass, thereby further avoiding pit damage and improving the strength of the glass.

[0033] Preferably, in step S3, the acid-resistant protective coating is removed by soaking in an organic solvent;

[0034] Preferably, the organic solvent is at least one of toluene, xylene, acetone, acetic acid, ethyl ester, chloroform or styrene;

[0035] Preferably, the soaking temperature is 40-60°C and the soaking time is 5-10 minutes.

[0036] Compared with the prior art, the beneficial technical effects achieved by the present invention are as follows:

[0037] The present invention forms an upper chamfer and a lower chamfer at the junction between the upper plane, the lower plane and the end face of the ultra-thin flexible glass, and the sizes of the upper chamfer and the lower chamfer are limited to optimal values ​​by using appropriate parameters, thereby shortening the processing time and effectively improving its bending performance. The present invention also improves the etching efficiency, shortens the etching time, and uses ultra-fine fiber wires as a basket to support and fix the glass, effectively avoiding pit damage on the chamfered surface, thereby further improving the strength of the glass. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is a cross-sectional view of a first exemplary ultra-thin flexible glass product of the present invention;

[0039] Figure 2 A cross-sectional view of surface concave points of a first exemplary ultra-thin flexible glass product of the present invention;

[0040] Figure 3 is a cross-sectional view of a second exemplary ultra-thin flexible glass product of the present invention;

[0041] Figure 4 is a cross-sectional view of a surface concave point of a second exemplary ultra-thin flexible glass product of the present invention;

[0042] Figure 5 is a cross-sectional view of a third exemplary ultra-thin flexible glass product of the present invention;

[0043] Figure 6 A cross-sectional view of a surface concave point of a third exemplary ultra-thin flexible glass product of the present invention;

[0044] Figure 7 is a cross-sectional view of a fourth exemplary ultra-thin flexible glass product of the present invention;

[0045] Figure 8 A cross-sectional view of a surface concave point of a fourth exemplary ultra-thin flexible glass product of the present invention;

[0046] Fig. 9 A physical picture of the chamfered cross section and surface concave points of the ultra-thin flexible glass product described in Example 1;

[0047] Fig.10 A physical picture of the chamfered cross section and surface concave points of the ultra-thin flexible glass product described in Example 2;

[0048] Fig.11 A physical picture of the chamfered cross section and surface concave points of the ultra-thin flexible glass product described in Comparative Example 1;

[0049] Fig.12 A physical picture of the chamfered cross section and surface concave points of the ultra-thin flexible glass product described in Comparative Example 2;

[0050] Fig.13 A physical picture of the chamfered cross section and surface concave points of the ultra-thin flexible glass product described in Comparative Example 3;

[0051] Fig.14 Schematic diagram of the extreme bending of ultra-thin flexible glass 2PB;

[0052] Fig.15 Schematic diagram of the dynamic bending test of ultra-thin flexible glass. DETAILED DESCRIPTION

[0053] Hereinafter, embodiments of the present invention will be described with reference to the drawings.

[0054] Figure 1FIG. 4 is a cross-sectional view of a first exemplary ultra-thin flexible glass product of the present invention, which shows a first exemplary bevel edge morphology of a chamfered portion. Figure 1 It can be seen that the ultra-thin flexible glass described in the present invention includes an upper surface 1, a lower surface 2, and an end face 4 connecting the upper plane 1 and the lower plane 2, and the end face 4 is a plane; an upper chamfered portion 8 is provided at the junction of the upper surface 1 and the end face 4, and a lower chamfered portion 9 is provided at the junction of the lower plane 2 and the end face 4, and the upper chamfered portion 8 and the lower chamfered portion 9 respectively have an inclined surface gradually protruding outward from the upper plane 1 or the lower plane 2 to the middle part of the end face 4; the chamfer width of the upper chamfered portion 8 is defined as W, the chamfer width of the lower chamfered portion 9 is defined as W', and the glass thickness is defined as T, W / T<0.5, W' / T<0.5. Figure 2 FIG. 1 is a cross-sectional view of a surface concave point of a first exemplary ultra-thin flexible glass product of the present invention. Figure 2 It can be seen that the concave point 3 is located at the edge of the lower chamfered portion 9 close to the end surface 4, and the size of the concave point is ≤0.01 mm.

[0055] Figure 3 FIG. 4 is a cross-sectional view of a second exemplary ultra-thin flexible glass product of the present invention, which shows a second exemplary bevel edge morphology of the chamfered portion. Figure 2 It can be seen that the ultra-thin flexible glass described in the present invention includes an upper surface 1, a lower surface 2, and an end face 5 connecting the upper plane 1 and the lower plane 2, and the end face 5 is a curved surface; an upper chamfered portion 8 is provided at the junction of the upper surface 1 and the end face 5, and a lower chamfered portion 9 is provided at the junction of the lower plane 2 and the end face 5, and the upper chamfered portion 8 and the lower chamfered portion 9 respectively have an inclined surface gradually protruding outward from the upper plane 1 or the lower plane 2 to the middle part of the end face 5; the chamfer width of the upper chamfered portion 8 is defined as W, the chamfer width of the lower chamfered portion 9 is defined as W', and the glass thickness is defined as T, W / T<0.5, W' / T<0.5. Figure 4 FIG. 1 is a cross-sectional view of a surface concave point of a second exemplary ultra-thin flexible glass product of the present invention. Figure 4 It can be seen that the concave point 3 is located at the edge of the lower chamfered portion 9 close to the end surface 5, and the size of the concave point is ≤0.01 mm.

[0056] Figure 5 FIG. 4 is a cross-sectional view of a third exemplary ultra-thin flexible glass product of the present invention, which shows a first exemplary curved edge morphology of a chamfered portion. Figure 5 It can be seen that the ultra-thin flexible glass described in the present invention includes an upper surface 1, a lower surface 2 and an end face 6 connecting the upper plane 1 and the lower plane 2, and the end face 6 is a plane; an upper chamfered portion 8 is provided at the junction of the upper surface 1 and the end face 6, and a lower chamfered portion 9 is provided at the junction of the lower plane 2 and the end face 6, and the upper chamfered portion 8 and the lower chamfered portion 9 respectively have a curved surface gradually protruding outward from the upper plane 1 or the lower plane 2 to the middle part of the end face 6; the chamfer width of the upper chamfered portion 8 is defined as W, the chamfer width of the lower chamfered portion 9 is defined as W', and the glass thickness is defined as T, W / T<0.5, W' / T<0.5. Figure 6FIG. 1 is a cross-sectional view of a surface concave point of a third exemplary ultra-thin flexible glass product of the present invention, referring to FIG. Figure 6 It can be seen that the concave point 3 is located at the edge of the lower chamfered portion 9 close to the end surface 6, and the size of the concave point is ≤0.01 mm.

[0057] Figure 7 FIG. 4 is a cross-sectional view of a fourth exemplary ultra-thin flexible glass product of the present invention, which shows a second exemplary curved edge morphology of the chamfered portion. Figure 7 It can be seen that the ultra-thin flexible glass described in the present invention includes an upper surface 1, a lower surface 2, and an end face 7 connecting the upper plane 1 and the lower plane 2, and the end face 7 is a curved surface; an upper chamfered portion 8 is provided at the junction of the upper surface 1 and the end face 7, and a lower chamfered portion 9 is provided at the junction of the lower plane 2 and the end face 7, and the upper chamfered portion 8 and the lower chamfered portion 9 respectively have curved surfaces that gradually protrude outward from the upper plane 1 or the lower plane 2 to the middle part of the end face 7; the chamfer width of the upper chamfered portion 8 is defined as W, the chamfer width of the lower chamfered portion 9 is defined as W', and the glass thickness is defined as T, W / T<0.5, W' / T<0.5. Figure 8 FIG. 1 is a cross-sectional view of a surface concave point of a fourth exemplary ultra-thin flexible glass product of the present invention, referring to FIG. Figure 8 It can be seen that the concave point 3 is located at the edge of the lower chamfered portion 9 close to the end surface 7, and the size of the concave point is ≤0.01 mm.

[0058] The technical solutions of the present invention are described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.

[0059] Example 1

[0060] Reference Fig. 9 , this embodiment provides an ultra-thin flexible glass product with lossless chamfers, comprising an upper plane, a lower plane, and an end face connecting the upper plane and the lower plane, wherein the junction between the upper plane and the end face has an upper chamfered portion, and the junction between the lower plane and the end face has a lower chamfered portion;

[0061] The chamfer width of the upper chamfered portion is 0.0136 mm, the chamfer width W' of the lower chamfered portion is 0.0121 mm, the glass thickness T is 0.0317 mm, the ratio of W / T is 0.43, and the ratio of W' / T is 0.38;

[0062] The edges of the upper chamfered portion and the lower chamfered portion close to the end surface also have concave points, and the maximum size of the concave points is 0.0084 mm.

[0063] The method for preparing the ultra-thin flexible glass with lossless chamfer specifically comprises:

[0064] (1) An epoxy resin material (including bisphenol A epoxy resin, polyurethane modified epoxy resin, diethylenetriamine, and 4-(phenylthio)phenyl diphenylsulfonium hexafluorophosphate in a mass ratio of 10:5:1:1) was coated on the upper and lower surfaces of the ultra-thin flexible glass substrate by a scraping method, and the substrate was first baked in a high-temperature oven at 70°C for 20 minutes, and then irradiated with UV light at 600 mj / cm 2 The energy is cured for 10 minutes to form an acid-resistant protective coating;

[0065] (2) using a femtosecond laser device to cut and split the ultra-thin flexible glass substrate with an acid-resistant protective coating, wherein the size of the glass after cutting and splitting is 176.15 mm×87.4 mm;

[0066] (3) inserting the cut ultra-thin flexible glass substrate into the basket and fixing it; the rack at the lower end of the basket in contact with the edge of the glass is a polyethylene fiber line with a diameter of 0.3 mm;

[0067] (4) using an immersion tank to hold an etching solution, the etching solution includes hydrofluoric acid, sulfuric acid and pure water in a mass ratio of 3:5:92, and a immersion mother basket device is provided in the immersion tank, and the basket with the ultra-thin flexible glass substrate fixed thereon is placed in the immersion tank mother basket, and the immersion tank mother basket is immersed in the immersion tank in advance, so that the ultra-thin flexible glass substrate is completely immersed in the etching solution in the tank, and is immersed at 35° C. for 35 seconds. An acid-proof circulation pump is also installed at the lower end of the immersion tank, and the etching solution in the tank flows and circulates up and down after the acid-proof circulation pump acts, and the glass is driven by the flowing and circulating etching solution to be thrown up and down, and the frequency of the acid-proof circulation pump is 50 Hz;

[0068] (5) The basket with the ultra-thin flexible glass substrate fixed thereon is taken out from the immersion tank, and then immersed in acetone at 50° C. After standing for 5 minutes, the epoxy resin material on the upper and lower surfaces of the ultra-thin flexible glass substrate is removed, thereby obtaining the ultra-thin flexible glass product with lossless chamfers.

[0069] Example 2

[0070] Reference Fig.10 , this embodiment provides an ultra-thin flexible glass product with lossless chamfers, comprising an upper plane, a lower plane, and an end face connecting the upper plane and the lower plane, wherein the junction between the upper plane and the end face has an upper chamfered portion, and the junction between the lower plane and the end face has a lower chamfered portion;

[0071] The chamfer width of the upper chamfered portion is 0.0332 mm, the chamfer width W' of the lower chamfered portion is 0.0318 mm, the glass thickness T is 0.0723 mm, the ratio of W / T is 0.46, and the ratio of W' / T is 0.44;

[0072] The edges of the upper chamfered portion and the lower chamfered portion close to the end surface also have concave points, and the maximum size of the concave points is 0.0095 mm.

[0073] The method for preparing the ultra-thin flexible glass with lossless chamfer specifically comprises:

[0074] (1) The upper and lower surfaces of the ultra-thin flexible glass substrate were coated with epoxy resin material by a scraping method, and then placed in a high-temperature oven for 20 min at 70 °C, and then exposed to UV light at 600 mj / cm 2 The energy is cured for 10 minutes to form an acid-resistant protective coating;

[0075] (2) using a femtosecond laser device to cut and split the ultra-thin flexible glass substrate with an acid-resistant protective coating, wherein the size of the glass after cutting and splitting is 149.41 mm×72.85 mm;

[0076] (3) inserting the cut ultra-thin flexible glass substrate into the basket and fixing it; the rack at the lower end of the basket in contact with the edge of the glass is a polyethylene fiber line with a diameter of 0.5 mm;

[0077] (4) using an immersion tank to hold an etching solution, the etching solution includes hydrofluoric acid, sulfuric acid and pure water in a mass ratio of 3:5:92, and a immersion mother basket device is provided in the immersion tank, and the basket with the ultra-thin flexible glass substrate fixed thereon is placed in the immersion tank mother basket, and the immersion tank mother basket is immersed in the immersion tank in advance, so that the ultra-thin flexible glass substrate is completely immersed in the etching solution in the tank, and is immersed at 35° C. for 35 seconds. An acid-proof circulation pump is also installed at the lower end of the immersion tank, and the etching solution in the tank flows and circulates up and down after the acid-proof circulation pump acts, and the glass is driven by the flowing and circulating etching solution to be thrown up and down, and the frequency of the acid-proof circulation pump is 50 Hz;

[0078] (5) The basket with the ultra-thin flexible glass substrate fixed thereon is taken out from the immersion tank, and then immersed in acetone at 50° C. After standing for 5 minutes, the epoxy resin material on the upper and lower surfaces of the ultra-thin flexible glass substrate is removed, thereby obtaining the ultra-thin flexible glass product with lossless chamfers.

[0079] Example 3

[0080] Reference Fig. 9 , this embodiment provides an ultra-thin flexible glass product with lossless chamfers, comprising an upper plane, a lower plane, and an end face connecting the upper plane and the lower plane, wherein the junction between the upper plane and the end face has an upper chamfered portion, and the junction between the lower plane and the end face has a lower chamfered portion;

[0081] The chamfer width of the upper chamfered portion is 0.0136 mm, the chamfer width W' of the lower chamfered portion is 0.0121 mm, the glass thickness T is 0.0317 mm, the ratio of W / T is 0.43, and the ratio of W' / T is 0.38;

[0082] The edges of the upper chamfered portion and the lower chamfered portion close to the end surface also have concave points, and the maximum size of the concave points is 0.0084 mm.

[0083] The method for preparing the ultra-thin flexible glass with lossless chamfer is the same as that of Example 1, except that the etching solution in step (4) comprises hydrofluoric acid, sulfuric acid, water-soluble crown ether and pure water in a mass ratio of 3:5:0.1:91.9;

[0084] The water-soluble crown ether is prepared by adding 4'-aminobenzo-18-crown-6 and 3-glycidyloxypropyltrimethoxysilane in a molar ratio of 1:1 to a 1wt% sodium bicarbonate aqueous solution (pH adjusted to 8.5 with ammonia water), stirring the mixture at 60°C for 6h, and removing the solvent under reduced pressure to obtain the water-soluble crown ether.

[0085] Comparative Example 1

[0086] Reference Fig.11 , this comparative example proposes an ultra-thin flexible glass product with lossless chamfer, comprising an upper plane, a lower plane, and an end face connecting the upper plane and the lower plane, wherein the junction between the upper plane and the end face has an upper chamfered portion, and the junction between the lower plane and the end face has a lower chamfered portion;

[0087] The chamfer width of the upper chamfered portion is 0.0379 mm, the chamfer width W' of the lower chamfered portion is 0.0396 mm, the glass thickness T is 0.0327 mm, the ratio of W / T is 1.16, and the ratio of W' / T is 1.21;

[0088] The edges of the upper chamfered portion and the lower chamfered portion close to the end surface also have concave points, and the maximum size of the concave points is 0.0284 mm.

[0089] The method for preparing the ultra-thin flexible glass with lossless chamfer is the same as that of Example 1 except that the immersion time in step (4) is 5 minutes.

[0090] Comparative Example 2

[0091] Reference Fig.12 , this comparative example proposes an ultra-thin flexible glass product with lossless chamfer, comprising an upper plane, a lower plane, and an end face connecting the upper plane and the lower plane, wherein the junction between the upper plane and the end face has an upper chamfered portion, and the junction between the lower plane and the end face has a lower chamfered portion;

[0092] The chamfer width of the upper chamfered portion is 0.0109 mm, the chamfer width W' of the lower chamfered portion is 0.0112 mm, the glass thickness T is 0.036 mm, the ratio of W / T is 1.16, and the ratio of W' / T is 0.37;

[0093] The edges of the upper chamfered portion and the lower chamfered portion close to the end surface also have concave points, and the maximum size of the concave points is 0.0138 mm.

[0094] The method for preparing the ultra-thin flexible glass with lossless chamfers is the same as that of Example 1, except that the frequency of the acid-proof circulating pump in step (4) is 0 Hz.

[0095] Comparative Example 3

[0096] Reference Fig.13 , this comparative example proposes an ultra-thin flexible glass product with lossless chamfer, comprising an upper plane, a lower plane, and an end face connecting the upper plane and the lower plane, wherein the junction between the upper plane and the end face has an upper chamfered portion, and the junction between the lower plane and the end face has a lower chamfered portion;

[0097] The chamfer width of the upper chamfered portion is 0.0355 mm, the chamfer width W' of the lower chamfered portion is 0.0346 mm, the glass thickness T is 0.0296 mm, the ratio of W / T is 1.20, and the ratio of W' / T is 1.17;

[0098] The edges of the upper chamfered portion and the lower chamfered portion close to the end surface also have concave points, and the maximum size of the concave points is 0.0315 mm.

[0099] The method for preparing the ultra-thin flexible glass with lossless chamfers is the same as that of Example 1, except that the immersion time in step (4) is 5 minutes and the frequency of the acid-proof circulation pump is 0 Hz.

[0100] After the ultra-thin flexible glass products described in the embodiments and comparative examples were subjected to chemical tempering treatment under the same conditions, a bending performance test was performed, based on the results of the extreme bending test and the dynamic bending test.

[0101] The bending performance test is as follows:

[0102] 1. Extreme bending test, refer to Fig.14 , bend the ultra-thin flexible glass UTG and put it between two baffles, the two baffles squeeze the glass at a uniform speed until it breaks, and read the distance between the two plates when the glass breaks;

[0103] 2. Dynamic bending test, refer to Fig.15 , use transparent tape to bend and fix the ultra-thin flexible glass UTG on two bending platforms. The bending part is in the bending area, the non-bending area is completely fixed, the bending angle is switched between 0 and 180°, the bending radius is set to R1 to 2mm, the bending number is 20w / 30w times, and after the bending is completed, observe whether the glass is damaged.

[0104] Table 1 Comparison of bending properties of the ultra-thin flexible glass described in the embodiment and the comparative example

[0105]

[0106]

[0107] OK means there are no cracks or creases after bending.

[0108] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An ultra-thin flexible glass with lossless chamfer, characterized in that: It includes an upper plane, a lower plane, and an end surface connecting the upper plane and the lower plane; wherein the junction between the upper plane and the end surface has an upper chamfered portion, and the junction between the lower plane and the end surface has a lower chamfered portion; The ratio of the chamfer width / glass thickness of the upper chamfered portion and the lower chamfered portion is less than 0.

5.

2. The ultra-thin flexible glass with lossless chamfer according to claim 1, characterized in that: The glass thickness is ≤0.1 mm, preferably ≤0.07 mm, and more preferably ≤0.03 mm.

3. The ultra-thin flexible glass with lossless chamfer according to claim 1 or 2, characterized in that: The chamfer width of the upper chamfered portion is defined as W, the chamfer width of the lower chamfered portion is defined as W', and the glass thickness is defined as T; 0.3≤W / T<0.5, and 0.3≤W' / T<0.5; Preferably, 0.4≤W / T<0.5, and 0.4≤W′ / T<0.

5.

4. The ultra-thin flexible glass with lossless chamfer according to any one of claims 1 to 3, characterized in that: The upper chamfered portion and the lower chamfered portion have an inclined surface or a curved surface which gradually protrudes outward from the upper plane or the lower plane toward the middle portion of the end surface.

5. The ultra-thin flexible glass with lossless chamfer according to any one of claims 1 to 4, characterized in that: The surface pit size of the upper chamfered portion and the lower chamfered portion is ≤0.01mm.

6. A method for preparing the ultra-thin flexible glass with lossless chamfer according to any one of claims 1 to 5, characterized in that: The steps include: S1. After coating the upper and lower surfaces of the ultra-thin flexible glass substrate to form an acid-resistant protective coating, cutting to form a desired shape; S2, after the cut ultra-thin flexible glass substrate is completely immersed in the etching solution, the junctions of the upper plane and the lower plane with the end face are etched to form an upper chamfered portion and a lower chamfered portion; S3, removing the acid-resistant protective coating on the upper plane and the lower plane of the etched ultra-thin flexible glass substrate to obtain the ultra-thin flexible glass.

7. The method for preparing the ultra-thin flexible glass with lossless chamfer according to claim 6, characterized in that: In step S1, the acid-resistant protective coating is formed by UV curing of a high molecular weight acid-resistant organic material; Preferably, the high molecular weight acid-proof organic material is an acrylate-based free radical polymerization resin or an epoxy-based cationic polymerization resin.

8. The method for preparing the ultra-thin flexible glass with lossless chamfer according to claim 6 or 7, characterized in that: In step S2, the cut ultra-thin flexible glass substrate is fixed by inserting into a basket and then immersed in an etching solution; Preferably, the rack at the lower end of the basket in contact with the edge of the ultra-thin flexible glass substrate is a polymer organic fiber line, and the polymer fiber line is preferably a polyethylene fiber line or a polypropylene fiber line, and the diameter of the polymer organic fiber line is preferably ≤1 mm.

9. The method for preparing the ultra-thin flexible glass with lossless chamfer according to any one of claims 6 to 8, characterized in that: In step S2, the etching solution includes hydrofluoric acid and an inorganic acid, and the inorganic acid is at least one of sulfuric acid, hydrochloric acid or nitric acid; Preferably, the etching temperature is 20-40°C and the time is 30-60s; Preferably, during the etching process, a circulation pump is used to drive the etching solution to circulate up and down.

10. The method for preparing the ultra-thin flexible glass with lossless chamfer according to any one of claims 6 to 9, characterized in that: In step S3, the acid-resistant protective coating is removed by soaking in an organic solvent; Preferably, the organic solvent is at least one of toluene, xylene, acetone, acetic acid, ethyl ester, chloroform or styrene; Preferably, the soaking temperature is 40-60°C and the soaking time is 5-10 minutes.